Análise da conformidade de laudos de inspeção predial à ABNT NBR 16747:2020 e às legislações aplicáveis - Macedo dos Santos, Rebeca (Universidade Federal de São Carlos, 2026)
Regular building inspections and maintenance, carried out according to technical criteria by specialized professionals, are essential to ensure the safety, functionality, and durability of structures. This dissertation aimed to analyze the compliance of a sample of building inspection reports with the parameters outlined in ABNT NBR 16747 (2020). The specific objectives included analyzing the historical development of standards and regulations related to building inspection in Brazil, relating applicable legislation to the provisions of ABNT NBR 16747 (2020), investigating normative requirements associated with document management, and evaluating the relevance of technical documentation in the building inspection process. The research adopted a methodological approach comprising a literature review, document analysis, and a critical analysis of applicable legislation. In addition, a verification instrument grounded in the requirements of ABNT NBR 16747 (2020) was developed and used to analyze 21 technical reports on buildings of different typologies qualitatively and uses. The results revealed gaps and inconsistencies in the analyzed reports, particularly in document management, descriptions of building systems, and references to applicable legislation. The absence or insufficiency of technical documents compromises the reliability of the analyses and hinders the proper characterization of the identified irregularities. Furthermore, significant variability was observed in the application of the criteria established by ABNT NBR 16747 (2020), demonstrating the need for greater standardization and professional training. It is concluded that document management plays a strategic role in building inspections and is essential for ensuring the quality and reliability of technical reports.
Analysis of the compliance of a sample of building inspection reports with ABNT NBR 16747:2020 and applicable regulations
Keywords: Inspeção predial; Laudo técnico; Gestão documental; NBR 16747:2020; Building inspection; Technical report; Document management; NBR 16747:20; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; 9. Indústria, Inovação e Infraestrutura; 11. Cidades e Comunidades Sustentáveis